Interpreting change from patient reported outcome (PRO) endpoints: patient global ratings of concept versus patient global ratings of change, a case study among osteoporosis patients. Issue 1 (December 2016) - Nixon, Annabel; Doll, Helen; Kerr, Cicely; Burge, Russel; Naegeli, April
Abstract Background Regulatory guidance recommends anchor-based methods for interpretation of treatment effects measured by PRO endpoints. Methodological pros and cons of patient global ratings of change vs. patient global ratings of concept have been discussed but empirical evidence in support of either approach is lacking. This study evaluated the performance of patient global ratings of change and patient global ratings of concept for interpreting patient stability and patient improvement. Methods Patient global ratings of change and patient global ratings of concept were included in a psychometric validation study of an osteoporosis-targeted PRO instrument (the OPAQ-PF) to assess its ability to detect change and to derive responder definitions. 144 female osteoporosis patients with (n = 37) or without (n = 107) a recent (within 6 weeks) fragility fracture completed the OPAQ-PF and global items at baseline, 2 weeks (no recent fracture), and 12 weeks (recent fracture) post-baseline. Results Results differed between the two methods. Recent fracture patients reported moreimprovement while patients without recent fracture reported morestability on ratings of change than ratings of concept. However, correlations with OPAQ-PF score change were stronger for ratings of concept than ratings of change (both groups). Effect sizes for OPAQ-PF score change increased consistently with level of change in ratings of concept but inconsistently with ratings of change, with the mean AUC for prediction of a one-point change being 0.72 vs. 0.56. Conclusions This study provides initial empirical support for methodological and regulatory recommendations to use patient global ratings of concept rather than ratings of change when interpreting change captured by PRO instruments in studies evaluating treatment effects. These findings warrant being confirmed in a purpose-designed larger scale analysis.